Association of thyroid-stimulating hormone and lipid levels with suicide attempts among adolescents with major depressive disorder in China - Zhang, Qing; Zhao, Shuyi; Liu, Zhichun; Luo, Bei; Yang, Yingying; Shi, Yudong; Geng, Feng; Xia, Lei; Zhang, Kai; Liu, Huanzhong (Frontiers in Psychiatry, 2023)
Abstract Objectives: Evidence suggested that thyroid-stimulating hormone (TSH) and lipid levels were associated with major depressive disorder (MDD). However, its role in suicide attempts in adolescents with MDD was unclear. This investigation was to probe into the relationship between TSH, lipid levels and attempted suicide in adolescents with MDD. Methods: 179 adolescents with MDD were included from January 2021 to January 2022. Socio-demographic data and clinical data were obtained through self-made questionnaires. TSH and lipid levels were analyzed by a recognized laboratory. The Epidemiological Studies Depression Scale (CES-D) was used to assess the severity of depression. Questions about whether there was a behavior of suicide attempts were completed through conversation interviews. Results: Results showed that the CES-D, TSH, and low-density lipoprotein cholesterol (LDL-C) of suicide attempters were significantly higher than those of non-suicide attempters. Ordinary family relationships were more likely to attempt suicide than good family relationships. The CES-D score, ordinary family relationship, TSH and LDL-C were still significant in binary logistic regression, with an adjusted odds ratio (OR) of 1.04, 3.42, 5.14, and 1.76, respectively. The area under the receiver operating characteristic (ROC) curve showed that the area under the ROC curve (AUC) ranged from 0.60 to 0.74. Conclusions: Suicide attempts are common among adolescents with MDD and were associated with CES-D score, ordinary family relationships, TSH, and LDL-C. Given the association between suicide attempts and TSH and LDL-C, the dynamic changes in TSH and LDL-C levels should be detected regularly.